Analysis of Factors Influencing the Percentage of Poverty in North Sumatra Using Robust Linear Regression - Liyanti Angun Silaban; Susiana (PT FORMOSA CENDEKIA GLOBAL, 2023)
The percentage of poverty in North Sumatra Province in 2021 will reach 9.01%. The data used are poverty percentage data in North Sumatra for 2021, Gini ratio, Covid-19 pandemic, poverty depth index, education and unemployment rate are considered to contribute to the percentage of poverty in North Sumatra Province. The purpose of this research is to determine the variables that have a significant effect on the Percentage of Poverty in North Sumatra in 2021. The method used is Ordinal Least Square. The results of this study show that the Poverty Percentage model in North Sumatra in 2021 uses a robust M-estimation regression which is 4.432790; 0.07230 and 0.007035. Partially, the regression coefficient shows that the poverty depth index has a significant effect on the percentage of poverty with a probability of 9.087. Simultaneously, the Gini ratio, the Covid-19 pandemic, the poverty depth index, education and unemployment affect the percentage of poverty with a probability of 64,602.